Traditional Chinese medicine body constitutions and psychological determinants of depression among university students in Malaysia: a pilot study - Yap, Sin Yee; Foo, Chai Nien; Lim, Yang Mooi; Ng, Foong Leng; Mohd Sidik, Sherina; Tang, Pek Yee; Najar Singh, Jagjit Kaur; Pheh, Kai Shuen (Multidisciplinary Digital Publishing Institute, 2021)
Depression is commonly observed in university students, who are a high risk group for developing psychiatric disorders during adulthood. This study aimed to determine the prevalence of depression and its traditional Chinese medicine body constitutions and psychological determinants among university students in Malaysia. A cross-sectional pilot study was conducted between 9 and 28 September 2020 among 80 university students in Malaysia. Participants completed online survey questionnaires, including the validated Patient Health Questionnaire (PHQ-9), Constitution in Chinese Medicine Questionnaire (CMCQ), Dysfunctional Attitude Scale (DAS), Depression Anxiety Stress Scale (DASS-21) stress subscale, Perceived Stress Scale (PSS-10), and Rosenberg Self-Esteem Scale (RSES), which assess depression, body constitution, dysfunctional attitude, stress, perceived stress, and self-esteem. Multiple linear regression analyses were performed to determine the associated risk factors for depression. The overall prevalence of depression among university students was 33.8%. The multiple regression analysis showed a significant relationship between depression and qi-stagnation constitution (B = 0.089, p = 0.011), balanced constitution (B = −0.077, p = 0.049), and self-esteem (B = −0.325, p = 0.001). Our findings suggest that some traditional Chinese medicine body constitutions and self-esteem are significant risk factors affecting depression among university students. Identifying risk factors of depression is vital to aid in the early detection of depression among university students.